2019
DOI: 10.1108/jsma-01-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Corporate culture and stock returns: evidence from Indian companies

Abstract: Purpose The purpose of this paper is to investigate the stock market performance of companies featured in the survey “Best Companies to Work For” as a proxy for corporate culture. Design/methodology/approach The authors employed the portfolio formation and event study methods from finance to examine the linkage between corporate culture and future stocks returns. The lists of India’s best place to work for by Great Place to Work® Institute and Business Today (BT), India’s leading business magazine, form the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In the SME literature, the influence of organizational culture on firm performance abounds (Brettel et al, 2015;Dabi c et al, 2018;Fatima and Bilal, 2019;Aziz et al, 2019). Morgan (2000) asserts that the integration of culture and strategy creates the strategic direction of the firm and consequently determines competitiveness.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…In the SME literature, the influence of organizational culture on firm performance abounds (Brettel et al, 2015;Dabi c et al, 2018;Fatima and Bilal, 2019;Aziz et al, 2019). Morgan (2000) asserts that the integration of culture and strategy creates the strategic direction of the firm and consequently determines competitiveness.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…A company, which has a valuable, rare and imperfectly imitable culture is successful in having a sustainable competitive advantage (Barney, 1991). Aziz et al (2019) found that Indian companies that got recognition in the "Best Companies to Work For" list gave more returns than the market index. Corporate culture is a necessity for not only competitive advantage but also to retain skilled employees within the organization who are vital for its growth (Sadri and Lees, 2001).…”
Section: Corporate Culturementioning
confidence: 99%
“…Strategic thinking can help a firm in gaining a competitive advantage through specialized human and perceptual abilities (Shaik and Dhir, 2020). The study of literature has shown that the identified antecedents of strategic thinking (vision, creativity, corporate culture and knowledge management) are related to competitive advantage (Tripathi and Ghosh, 2020;Aziz et al, 2019;Lyndon and Pandey, 2019;Khan, 2016;Self et al, 2015). However, studies in the extant literature lack the answer to whether strategic thinking plays a role of mediator on the relationship between competitive advantage and antecedents.…”
Section: Antecedents Of Strategic Thinkingmentioning
confidence: 99%